Histology and External Morphological Assessment on Ovarian Maturation Stages of Wild Female Banana Shrimp, Penaeus merguiensis (de Man, 1888) for Broodstock Selection Purpose - Hidayah Manan,; Adnan Amin-Safwan,; Irma Wahida Shakri,; Nor Azman Kasan,; Mhd Ikhwanuddin, (Tropical Life Sciences Research, 2022)
Study on ovarian maturation stages were carried out using external morphological assessment of ovarian colourations and histological assessment of Oocyte structure for broodstock selection purpose. Stage 1 to Stage 4 of female shrimps broodstock were sampled from Kuala Muda, Kedah, Malaysia. Four obvious colourations of ovary stages were identified which are: yellow (Stage 1), green yellowish (Stage 2), light greenish (Stage 3) and dark green (Stage 4) through the morphological assessment. The Gonadosomatic Index (GSI) showed significant increment as the gonad reach advance stages. Histological assessment of Stage 1 ovary identified perinucleolar oocyte (PO) with small size oocytes. Stage 2 ovary was identified with yolkless oocyte (YO), Stage 3 ovary was identified with late stage of yolky globules and Stage 4 ovary was identified with fully yolky globules. From the results achieved, it can be concluded that the ovarian colourations and GSI can be applied to identify the ovarian maturation stages, meanwhile, the histology assessment is the most precise method to determine the ovarian maturation stages in more details and accurate for each of the ovarian maturation stages. Kajian mengenai peringkat kematangan ovari telah dijalankan menggunakan penilaian morfologi luaran pewarnaan ovari dan penilaian histologi struktur oosit untuk tujuan pemilihan induk. Peringkat 1 hingga Peringkat 4 induk udang betina telah diambil sampel dari Kuala Muda, Kedah, Malaysia. Empat warna jelas peringkat ovari telah dikenal pasti iaitu: kuning (Peringkat 1), hijau kekuningan (Peringkat 2), hijau muda (Peringkat 3) dan hijau gelap (Peringkat 4) melalui penilaian morfologi. Indeks Gonadosomatic (GSI) menunjukkan peningkatan yang ketara apabila gonad mencapai peringkat lebih tinggi. Penilaian histologi ovari Peringkat 1 mengenal pasti perinucleolar oocyte (PO) dengan oosit saiz kecil. Ovari Peringkat 2 telah dikenal pasti dengan yolkless oocyte (YO), ovari Peringkat 3 telah dikenal pasti dengan peringkat akhir globul kuning dan ovari Peringkat 4 telah dikenal pasti dengan globul kuning sepenuhnya. Dari keputusan yang dicapai, dapat disimpulkan bahawa pewarnaan ovari dan GSI boleh digunakan untuk mengenal pasti peringkat kematangan ovari, sementara itu, penilaian histologi merupakan kaedah yang paling tepat untuk menentukan peringkat kematangan ovari dengan lebih terperinci dan tepat untuk setiap peringkat.